Stylistic Analysis of Laxmi Prasad Devkota’s Poem ’The Lunatic’ - Shahi, Sushil Kumar (Journal of Nepalese Management and Research, 2023)
This study is based on a stylistic analysis of the poem ’The Lunatic’ by a great modern poet of Nepal, Laxmi Prasad Devkota. This analysis focuses on the foregrounding, metaphors, graphological, phonological, morphological, and semantic levels to explore and analyze what the poet wants to convey by describing his own experiences, showing the complex relationship between the poet and people living in the society that is going through social transformation. Stylistic techniques and methods are tactfully used to unfold the hidden feelings and experiences of the poet’s life. Keeping in view stylistics is the study of different devices employed in language that give literary style and beauty to any writing; this article aims to explore and reveal hidden realities of poetic lines used in the poem ’The Lunatic’. This analysis helps us understand the poetic expression that can beautifully provide the picture of social transformation through the conflict between the poet and society. The stylistic devices used in this poem are the setting of the poem, along with the figures of speech. This study examines how the changing social context affects the poet’s feelings and thoughts when composing poetry. Furthermore, the article explores how figurative speech enhances the impact of poetry on the readers’ thinking.